METHODS FOR RECYCLING PHOTOVOLTAIC MODULES AND ELEMENT RECOVERY PROJECTIONS IN SLOVENIA - Obreza, Manja; Friškovec, Nejc; Sredenšek, Klemen; Seme, Sebastijan (Journal of Energy Technology, 2025)
This paper aims to present different methods of recycling photovoltaic modules, which were researched by different institutes. Significant importance has been attributed to photovoltaic modules in the Renewable Energy sector, thereby contributing to the global transition towards sustainable energy sources. However, as the lifespan of these modules comes to an end, effective recycling methods will become crucial to minimize the environmental impact and resource depletion. This paper highlights recent advancements in photovoltaic module recycling technologies, focusing on predicting the potential mass of a specific element that could be recovered through recycling in Slovenia, considering the installed capacity of solar power plants, which is approximately 1105 MW. A projection of materials that can be obtained through the recycling process of photovoltaic modules was conducted based on current installed capacity, and it was discovered that up to 2150 tons of silicon and 1025 tons of copper could be obtained by the recycling process. The acquisition of various materials would have a significant role in the production of new photovoltaic modules, thereby enabling sustainable manufacturing and contributing substantially to the circular economy.